2018
DOI: 10.1002/etc.4258
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chronic toxicity of sodium chloride or potassium chloride to a unionid mussel (Lampsilis siliquoidea) in water exposures using standard and refined toxicity testing methods

Abstract: Freshwater mussels are generally underrepresented in toxicity databases used to derive water quality criteria, especially for long-term exposures. Multiple tests were conducted to determine the chronic toxicity of sodium chloride (NaCl) or potassium chloride (KCl) to a unionid mussel (fatmucket, Lampsilis siliquoidea). Initially, a 4-wk NaCl test and a 4-wk KCl test were conducted starting with 2-mo-old mussels in water exposures with and without a thin layer of sand substrate. A feeding study was conducted la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 46 publications
3
57
0
Order By: Relevance
“…A previous study on the unionid mussel (Lampsilis siliquoidea) in 28-day chronic toxicity tests to ammonia, conducted with soil substrate ranging in size of 300 to 500 µm and conducted without any, similarly found that the presence of a substrate did not influence the toxicant sensitivity of this freshwater mussel [46]. However, the same author conducted more recently another study based on the same experimental test on chronic toxicity to NaCl and potassium chloride (KCl) with silica sand (particle size of 100 to 400 µm) used as substrate and reported that EC20, based on biomass endpoint, in substrate presence, was twofold lower than without substrate [47]. This indicates that the mussel responses in the presence or absence of substrate might be dependent on the exposure duration and might differ according to the endpoint studied.…”
Section: Methodsmentioning
confidence: 88%
“…A previous study on the unionid mussel (Lampsilis siliquoidea) in 28-day chronic toxicity tests to ammonia, conducted with soil substrate ranging in size of 300 to 500 µm and conducted without any, similarly found that the presence of a substrate did not influence the toxicant sensitivity of this freshwater mussel [46]. However, the same author conducted more recently another study based on the same experimental test on chronic toxicity to NaCl and potassium chloride (KCl) with silica sand (particle size of 100 to 400 µm) used as substrate and reported that EC20, based on biomass endpoint, in substrate presence, was twofold lower than without substrate [47]. This indicates that the mussel responses in the presence or absence of substrate might be dependent on the exposure duration and might differ according to the endpoint studied.…”
Section: Methodsmentioning
confidence: 88%
“…Both the short duration of the experiment and the use of a limited number of adult specimens for each exposure limits the conclusions that can be drawn regarding mortality rates (e.g., LC50 values). The influence of salt content or duration of exposure on mussel mortality could not be determined due to the similar mussel response in both the low and high dose treatments, but previous studies demonstrate the importance of both chloride and water hardness when assessing mortality [33][34][35]83,84 . Because our study utilized a relatively small number of individuals, a different genera, and adult mussels compared to previous studies, mortality rates were not thoroughly evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…A limited number of studies have examined freshwater mussels exposed to high salinity water. Unionid mussels (Lampsilis Siliquoidea) exposed to elevated salinity in the form of high Cl concentrations from KCl and NaCl salts or synthetic inorganic mixtures that represent produced waters resulted in increased mortality and decreased growth [33][34][35] . In cages placed downstream of an oil and gas discharge, high mortality was observed in riffleshell mussels (Epioblasma torulosa rangiana) 36 .…”
mentioning
confidence: 99%
“…Replicate beakers in each diluter were held in a water bath at 23 ± 1 °C. Mussels were fed 2 mL of algal mixture (~510 nL cell volume/L) delivered by a peristaltic pump (Dosing Pump; Jiyang Aquarium Equipment) automatically into each replicate beaker with each cycling of diluter (Wang et al 2018a). The algal mixture was prepared daily by adding 1 mL of a commercial nonviable microalgal Nannochloropsis concentrate (Nanno 3600 TM ) and 2 mL of a mix of 6 microalgae (Shellfish Diet 1800 TM ; Reed Mariculture) into 1.8 L of test water.…”
Section: Methodsmentioning
confidence: 99%